EFEKTIVITAS MEDIA GATHER TOWN DALAM PEMBELAJARAN KETERAMPILAN BERBICARA BAHASA JERMAN - Tirtosaid Sudrajat, - (2023)
In learning German language skills, speaking skill is one of the important language abilities to be mastered so that learners can express their ideas and opinions orally. However, learners still face difficulties in this regard. The problems faced by learners are suspected to be caused by various factors, including low motivation and interest, inadequate learning environment, and reluctance to speak in German. One solution to motivate learners to speak in German is to use engaging media. Gather Town is an interactive virtual platform that allows learners to interact with their peers in a 2D gamelike environment. The abundance of virtual locations in Gather Town is assumed to capture learners' interest and provide a supportive learning environment. The objectives of this research are to determine: 1) The speaking skills of learners before the implementation of Gather Town; 2) The speaking skills of learners after the implementation of Gather Town; 3) The difference in speaking skills of learners before and after the implementation of Gather Town; 4) The effectiveness of Gather Town in teaching speaking skills; and 5) The learners' response to the implementation of Gather Town in German speaking skill learning. This research is a quantitative study using a Quasi Experiment. The population consisted of students in the XI grade who chose German as an elective subject at SMAN 15 Bandung in the academic year 2022/2023. The research sample consists of 15 students from XI MIPA 6 as the experimental group and 15 students from XI MIPA 7 as the control group. The results of the research show that: 1) The learners' speaking skills in both the experimental and control groups before the treatment are categorized as poor; 2) The learners' speaking skills in the experimental group after the treatment are categorized as fair, while it remained poor in the control group; 3) There is a significant difference in German speaking skills between the experimental and control groups; 4) The effectiveness of the Gather Town platform is determined by the results of the two-tailed t-test calculation with a significance value less than 0.05 (0.048 < 0.05); and 5) The questionnaire results show a positive response from the learners towards the use of Gather Town platform in learning German speaking skill. To optimize the use of Gather Town in the classroom, it is recommended to consider the stability of internet connectivity and the availability of suitable devices.